Tailored treatment of specific diagnosis improves symptoms and quality of life in patients with myocardial Ischemia and Non-obstructive Coronary Arteries - Piotr Szolc; Bartłomiej Guzik; Łukasz Niewiara; Paweł Kleczyński; Anna Bernacik; Marta Diachyshyn; Maciej Stąpór; Krzysztof Żmudka; Jacek Legutko (Scientific Reports)
Abstract Ischemia and non-obstructive coronary arteries (INOCA) represents a challenging clinical scenario affecting a considerable proportion of patients undergoing coronary angiography. INOCA manifests with various pathomechanisms, including abnormalities in coronary microvessels and vasomotor disorders. INOCA patients experience substantial symptoms and heightened risk of adverse cardiac events. Guidelines outline diagnostic and treatment strategies, emphasizing tailored approaches for improved outcomes. This study aimed to evaluate symptoms and quality of life changes in INOCA patients following tailored treatment based on comprehensive diagnostic assessment of the coronary circulation. This is a single-center prospective registry of symptomatic adult patients diagnosed with INOCA. Comprehensive invasive physiological diagnostics including assessment of coronary microcirculation function and coronary artery reactivity were conducted. Clinical outcomes, angina severity (Canadian Cardiovascular Scale), and quality of life (SF-36 questionnaire) were assessed at baseline and after 12 months of tailored anti-angina treatment based on pathophysiological background. A total of 150 patients were enrolled. At baseline 8% of patients had angina CCS I, 70% CCS II and 22% CCS III. After 12 months 46% had no angina symptoms, 22% had angina CCS I, 26% CCS II and 6% CCS III. Following tailored treatment, angina severity significantly decreased (p < 0.001). The quality of life (SF-36 questionnaire) was significantly better after 12 months compared to baseline (66 [45; 103] vs. 91 [69; 115] points; P < 0.001). In this observational study, a proposed care pathway for patients with INOCA was presented. Despite the observational nature of the study, both symptoms and quality of life improved, underscoring the need for future prospective randomized controlled trials. Further research, including adequately powered sample sizes of patients is warranted to evaluate the influence of pathophysiology-tailored treatment of INOCA on long-term major cardiovascular events.